A entoação avaliativa na defesa criminal no tribunal do júri: contribuições da Teoria Dialógica da Linguagem - Oliveira, Antonio Flávio Ferreira de (2015)
This research investigates the manner of how a defensive lawyer, in the Court, evaluates the social auditorium as well as how this evaluation stablishes the language style used for creating an entry-conscience into the jury. From this perspective, the objective of this study is to verify, in the criminal defense, how the defense lawyer’s discourse is influenced by the social auditorium. Thus, to support the research, they were used the theoretical-methodological bases of Dialogical Theory of Language (DTL) established by Bakhtin’s Circle, Voloshinov ([1976]); Voloshinov ([2005]); Bakhtin/Volochínov (2009); Bakhtin (2010a, 2010b, 2010c, 2011, 2012). To explain and interpret the facts they were used the principles of the qualitative-interpretative research. The corpus is consisted of one (01) criminal defense that happened in Court of Guarabira-PB town. The choice of the criminal defense was carried out due to the possibilities of evaluative intonations that were found in the lawyer’s defensive discourse. In the sample they could be stablished seven (07) categories of evaluative intonations. The analyses have evidenced that, from the evaluative intonations, the lawyer uses some discursive strategies established by a language style characterized of subjective constitution.